Un/Learning the Suffragette in Kate Muir’s Suffragette City and Lisa Evans’ Old Baggage - Ripoll Fonollar, Mariana (Complutense Journal of English Studies, 2025)
This article focuses on the instructive protagonists of Kate Muir’s Suffragette City (1999) and Lisa Evans’ Old Baggage (2018) in what regards their revisionist didacticism of the British suffragette movement. The narrative devices deployed by Muir and Evans will be analyzed as revealing the novels’ double didactic value as pedagogic tools for characters and readers. I argue that Muir and Evans do not seek to gain supporters for a cause already accomplished, but to fill in existent gaps in the historical record about such a crucial part of feminist history. The use of different narrative elements − epistolary fragments in Suffrage City and lectures and speeches in Old Baggage − confer these novels with an educational tone helping readers un/learn certain aspects of the women’s campaign for the vote. Ultimately, I seek to prove that the authors offer an insight of the suffrage movement that stems from the revision and disclaim of wrong assumptions and ideas about the Cause. In this respect, I argue that the novels urge readers to learn about the women’s movement and challenge preconceived notions about this historical period achieving this double purpose by emphasising the role of the suffragette as educator and mentor.